한방부인과 진단용 설문지의 신뢰도 연구 - 이인선(In Sun Lee); 전란희(Ran Hee Jeon); 배경미(Kyung Mi Bae); 김미진(Mi Jin Kim); 엄윤경(Yun Kyung Yeum); 이용태(Yong Tae Lee); 지규용(Gyu Yong Ji); 김종원(Jong Won Kim); 김규곤(Gyu Gon Kim) (동의생리병리학회지, 2004)
This study investigated reliability of Oriental OB & GY Questionnaires, evaluated the items and correlation relation of differentiation of syndromes of Oriental OB&GY Questionnaires which was used by Dong-Eui OB&GY. We analyzed the results of 553 outpatients's Questionnaires from April 2002 to February 2004. The reliability of Oriental OB&GY Questionnaires above 95% was stagnated blood most, above 90% deficiency of blood, deficiency of Um, heat syndrome, dampness, kidney, liver, heart, spleen, with the exception of phlegm all that was above 80%. The frequency diagnosed of items of differentiation of syndromes dampness, hear, stagnation of Ki was most, the average of item of differentiation of syndromes stagnation of Ki, dampness, deficiency of Ki was most. Correlation coefficient of deficiency of Ki, deficiency of blood, deficiency of Um, cold syndrome, heat, stagnated blood, heart, spleen, kidney, dryness, stagnation of Ki, liver with more than pure question was above 0.8, phlegm was under 0.5. The frequency diagnosed of items of the differentiation of syndromes was not which is related to repeated question and physiology and pathology of oriental medicine.